Assessing the Effects of Physical Barriers and Hypoxia on Red Drum Movement Patterns to Develop More Effective Management Strategies - Steven M. Baker; Eric A. Reyier; Bonnie J. Ahr; Geoffrey S. Cook (Fishes, 2023)
Human modification of coastal ecosystems often creates barriers to fish movement. Passive acoustic telemetry was used to quantify movement patterns and habitat use of red drums (Sciaenops ocellatus) within and around a complex of coastal impoundments, and explored how the presence of artificial structures (i.e., bollards and culverts) and a hypoxia-related mortality event impacted fish movement. Results indicated bollards impede the movement of individuals with head widths greater than the mean distance between bollards (~16.0 cm). Red drum home range area and daily distance traveled were related to water dissolved oxygen concentrations; as oxygen levels decreased, fish habitat use area decreased initially. However, continued exposure to hypoxic conditions increased fish cumulative daily distance traveled. When exposed to anoxic waters, fish daily distance traveled and rate of movement were greatly reduced. These findings suggest prolonged exposure to low dissolved oxygen in combination with artificial structures can reduce movement of red drum, increase risk of mortality, and decrease habitat connectivity. Constructing and maintaining (sediment and biofouling removal) larger culvert openings and/or using wider bollard spacing would improve water circulation in impoundments, increase habitat connectivity, and facilitate movement of large sportfish inhabiting Florida’s coastal waters.